Modeling the interactions among Salmonella enteritidis, Pseudomonas aeruginosa, and Lactobacillus plantarum. Issue 4 (23rd April 2020) - Chen, Yuanmei; Wang, Xiang; Zhang, Xibin; Xu, Dongpo; Zhang, Wenmin; Qiu, Jingxuan; Liu, Qing; Dong, Qingli
Abstract: This paper was to investigate the interactions among Salmonella enteritidis, Lactobacillus plantarum, and Pseudomonas aeruginosa at four combinations of initial concentration. Firstly, fitting the growth curves to obtain growth parameters—lag time ( λ ), maximal growth rate ( μ max ), initial concentration ( N 0 ), and maximum population density ( N max ) for each strain in monocultures or cocultures. Then interactions among S. enteritidis, P. aeruginosa, and L. plantarum in cocultures at four combinations of initial concentration were quantified by the Lotka–Volterra model with six interaction coefficients. Results indicated that there were no interactions between S. enteritidis and P. aeruginosa ; S. enteritidis and P. aeruginosa had an inhibitory effect on L. plantarum, but L. plantarum had no effects on another two. Besides, the higher the initial concentrations of S. enteritidis or P. aeruginosa, the lower the growth potential of L. plantarum . This study provided more accurate predictions for the growth of bacteria under actual food contamination conditions. Abstract : S. enteritidis and P. aeruginosa had an inhibitory effect on L. plantarum . L. plantarum had no effects on S. enteritidis and P. aeruginosa . Lotka–Volterra model with six interaction coefficients could quantitatively describe the interaction among Salmonella enteritidis, Lactobacillus plantarum, and Pseudomonas aeruginosa .